The Effects of Anonymity in Business Ethics Class Discussions Using Various Gender Compositions - Murniadi, Krishnamurti; Trilaksono, Teddy (Indonesian Business Review, 2026)
The gender makeup of the group and anonymity have a significant impact on small group talks. Business Ethics is one business course that frequently incorporates debate. Anonymity is the state in which meeting attendees are unidentified, hence removing any physical clues, especially in corporate ethics case group discussions. The gender makeup of the group, on the other hand, is crucial to its level of attraction since members of the group tend to associate with people who are similar to them and to be prejudiced against those who are different. This study investigated if anonymity lowers the degree of attraction between groups with varying gender makeup. Participants were divided into six groups for the experiment. There were three groups that communicate in offline classroom settings and three groups that communicated via computer-mediated communication (CMC). In both settings, there were male-only groups, female-only groups, and mixed-gender groups. An actual gender-related case and four discussion questions were used to activate gender identification. Findings suggested that female-only groups members had significantly higher level of group attraction in offline classroom settings than CMC, while there was no significant difference in group attraction between offline and CMC settings in in male-only and mixed-gender groups.